Spacings between plants with chicken manure in Roselle crop - doi: 10.4025/actasciagron.v33i4.6933 - Ramos, Diovany Doffinger; Vieira, Maria do Carmo; Zárate, Néstor Antonio Heredia; Yamamoto, Natanael Takeo; Carnevali, Thiago Oliveira; Souza, Natália Hilgert (Acta Scientiarum. Agronomy, 2011)
The purpose of this work was to analyze the effects of plant spacing within rows by means of applying or not applying chicken manure to the soil cover in the growth and yields of roselle biomass. The treatments consisted of five spacings between plants (0.30, 0.35, 0.40, 0.45 and 0.50 m) and the application or non application of chicken manure to the soil cover in a dose of 10 ton. ha-1, arranged in randomized blocks of 5 x 2 with four replicates. The maximum plant height (282.92 cm) was achieved at 200 days after the transplant (DAT), with 0.35 m between plants and without the application of chicken manure. The leaf area was significantly influenced by the interaction of the spacings between plants and the application of chicken manure, presenting a linear growth of 32,009 cm2 plants-1. The biggest fresh and dry weight yields in leaves were 31,571 and 3,339 kg ha-1, respectively, with a 0.30 m spacing between the plants. The biggest yields of both fresh and dry weights of the stems and fruits of roselle plants were obtained in the soil with chicken manure.